Evidence for altered vascular responses to exogenous endothelin-1 in patients with advanced cirrhosis with restoration of the normal vasoconstrictor response following successful liver transplantation. Issue 10 (11th September 2003) - Vaughan, R B; Angus, P W; Chin-Dusting, J P F
Abstract : Background and aims: There is evidence that dampened responses to endogenous vasoconstrictors contribute to the hyperdynamic circulation that is characteristic of advanced cirrhosis. The aim of this study was to determine whether there is an altered vascular responsiveness to the endothelium derived constricting factor endothelin-1 (ET-1) in patients with decompensated chronic liver disease which might contribute to this abnormal circulatory state, and whether normal endothelin responses are restored following liver transplantation. Methods: Using forearm plethysmography, we studied the vascular response to an intra-arterial ET-1 infusion in six patients with end stage cirrhosis, before and after liver transplantation, compared with six normal control subjects. Responses to the selective endothelin A (ETA ) receptor subtype antagonist, BQ123, were also examined. Results: The forearm vessels of patients with cirrhosis vasodilated in response to ET-1 infusion while in healthy controls a marked vasoconstriction response was observed (p<0.0001, area under the curve time-blood flow was normal compared with the cirrhosis groups, ANOVA). Prior to commencement of liver transplant surgery, cirrhotic patients were confirmed to have a hyperdynamic circulation with a high cardiac index (4.07 (0.23) l/min/m 2 (normal range 2.8–3.6 l/min/m 2 )) and low systemic vascular resistance index (1284 (115) dyn×s/cm 5 /m 2 (normal range 1760–2600 dyn×s/cm 5 /m 2 )). Following transplantation, normal vasoconstrictor responses to ET-1 were restored. Responses to BQ123 were not different in patients with advanced cirrhosis compared with controls. Conclusion: In patients with end stage cirrhosis, ET-1 produces vasodilatation at a dose that causes marked vasoconstriction in normal control subjects. This effect is not attributable to impairment of ETA receptor responses. Our findings suggest that altered endothelin responses may contribute to the generalised dilatation of the circulation that occurs in patients with advanced liver disease.